Pemberdayaan Pelaku Usaha Melalui Digitalisasi UMKM Berbasis QRIS dan Google Maps di Desa Batu Karang - Muhammad Ridwan; Yenti Arsini; Randianto Alfandi; Siska Melida Saragih; Titi Atifah Zahra Maha; Vemi Fadila Sari (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This Community Service Program (Kuliah Kerja Nyata/KKN) aimed to empower Micro, Small, and Medium Enterprises (MSMEs) in Batu Karang Village through the adoption of digital technology, particularly the use of the Quick Response Code Indonesian Standard (QRIS) for non-cash transactions and Google Maps for improving business visibility. The program was conducted in response to the low level of digital literacy among local business actors and the continued dominance of manual, cash-based transaction systems, which often hinder efficiency and market expansion. A descriptive qualitative method was applied using a participatory approach that actively involved MSME owners in the implementation process. The activities included training on QRIS usage, assistance with business registration and location optimization on Google Maps, and ongoing digital operational support to ensure proper application. The results show that approximately 80% of MSMEs have successfully implemented QRIS as a payment method, while all participating businesses have been registered on Google Maps. The use of QRIS has improved transaction efficiency, security, and transparency, whereas Google Maps has expanded promotional reach and increased customer accessibility. Overall, this program has had a positive impact on enhancing digital literacy, strengthening business independence, and supporting sustainable, technology-based economic growth in rural areas.